Analysis of ums students' reception of the meaning of independence and freedom for gen-z in grab's advertisement: "Merdeka melaju dari A sampai Z" - Ningsih, Eva Alfia; Haryant, Yanti (The International Journal of Politics and Sociology Research, 2025)
This study aims to analyze the reception of students from Universitas Muhammadiyah Surakarta (UMS) towards the meaning of "independence" and "freedom" in the Grab advertisement "Merdeka Melaju dari A sampai Z." Using a qualitative descriptive method with the encoding-decoding reception analysis approach by Stuart Hall, this research categorizes the audience into three positions: dominant hegemonic, negotiated, and oppositional. Data was collected through interviews with five informants representing various study programs at UMS. The results show that the interpretation of the advertisement varies, influenced by individual backgrounds, experiences, and perceptions. Specifically, this study contributes to communication literature by enriching the understanding of how the values contained in the advertisement are perceived by Gen-Z audiences, as well as how personal experiences and social contexts influence the interpretation of the advertisement's message. The implications of this research are significant for communication and advertising practices, especially in designing campaigns that can more effectively respond to the diverse perceptions of young audiences who hold varied values and views on independence and freedom.